Satellite delivery of high-accuracy GNSS precise point positioning service: an overview for Australia. Issue 2 (4th May 2019) - Choy, Suelynn; Harima, Ken
Abstract: We present an overview of satellite delivery of GNSS precise corrections in support of Australia's planned National Positioning Infrastructure (NPI) capability. Specifically, we describe the requirements for satellite delivery of GNSS precise point positioning (PPP) corrections and local ionospheric corrections. We also provide an overview of potential and available L-band communication and navigation satellites in the region for the delivery of precise GNSS corrections.